Posterior Aortoplasty for Isolated Aortic Valve Replacement with Narrow Aorta’S Ostium - V. V. Popov; O. O. Bolshak; L. I. Tihonenko; O. V. Horoshkovataya; L. A. Klimenko; S. P. Spysarenko; T. A. Malysheva (Ukrainian Journal of Cardiovascular Surgery, 2016)
Purpose of this investigation is research of possibilities of reconstruction of aorta`s ostium and ascending aorta (RAOAA) during aortic valve replacement (AVR) in patents (pts) with narrow aorta`s ostium. In analyzed group were included 103 pts with aortic valve diseases and narrow aorta’s ostium who were operated in Institute from 01.05.2009 to 01.01.2016. AVR with RAOAA was performed in all cases by original methodic in which aorta’s incision was made in the middle of non-coronary leaflet, and then into central fibrous body of right trigone on depth 7–9 mm. Aorta’s segment in non-coronary leaflet was dissected in width of 1 cm. Vascutak`s patch 4x3 cm was replaced at the basement of non-coronary sinus and ascending aorta.Among 103 operated 7 pts died on during hospital period (30 days). There were no remarks to surgical correction. Peak systolic gradient on outlet of left ventricle was before operation 115,1±11,5 mm Hg, and on a aortic prosthesis at discharge 25,1±4,3 mm Hg.Reconstruction of narrow aorta’s ostium an ascending aorta during AVR by proposed method of posterior aortoplasty is highly effective intervention.